The concise encyclopedia of communication - Donsbach, Wolfgang, 1949- (Malden, MA : Wiley Blackwell, 2015)
This concise volume presents key concepts and entries from the twelve-volume ICA International Encyclopedia of Communication (2008), condensing leading scholarship into a practical and valuable single volume. Based on the definitive twelve-volume IEC, this new concise edition presents key concepts and the most relevant headwords of communication science in an A-Z format in an up-to-date mannerJointly published with the International Communication Association (ICA), the leading academic association of the discipline in the worldRepresents the best and most up-to-date international research in.
Communication Freedom in AsiaMedia Markets in Asia; References and Suggested Readings; Attending to the Mass Media; References and Suggested Readings; Attitude-Behavior Consistency; References and Suggested Readings; Attitudes; References and Suggested Readings; Audience Research; References and Suggested Readings; Audience Segmentation; References and Suggested Readings; Audiences, Female; References and Suggested Readings; Australia: Media System; References and Suggested Readings; B; Bad News in Medicine, Communicating; References and Suggested Readings; BBC.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Communication -- Encyclopedias; PSYCHOLOGY / Social Psychology; Communication; Communication -- Encyclopedias; Information theory -- Encyclopedias; Linguistics -- Encyclopedias; Electronic books; Encyclopedias